PSYCHOLOGICAL AND PEDAGOGICAL POSSIBILITIES OF FORMING TOLERANCE IN FUTURE TEACHERS (Uzbek Scholar Journal, 2022)
In this article, the psychological nature of tolerance and the importance of the formation of tolerance in future pedagogues today, the institutional model of the formation of tolerance are highlighted.